2018
DOI: 10.1042/cs20180121
|View full text |Cite
|
Sign up to set email alerts
|

Intratubular and intracellular renin–angiotensin system in the kidney: a unifying perspective in blood pressure control

Abstract: The renin-angiotensin system (RAS) is widely recognized as one of the most important vasoactive hormonal systems in the physiological regulation of blood pressure and the development of hypertension. This recognition is derived from, and supported by, extensive molecular, cellular, genetic, and pharmacological studies on the circulating (tissue-to-tissue), paracrine (cell-to-cell), and intracrine (intracellular, mitochondrial, nuclear) RAS during last several decades. Now, it is widely accepted that circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 156 publications
(398 reference statements)
1
49
0
Order By: Relevance
“…Angiotensin-I converting enzyme plays a key role in intrarenal vasoactive peptide systems. The enzyme transforms angiotensin I into angiotensin II inducing vasoconstriction and also inactivates bradykinin, a vasodilator peptide (Li et al, 2018). In our experiments, ACE immunolocalization was mainly present in the brush border of epithelial cells of proximal straight tubules although ACE had been localized also in mesangial cells and collecting duct (Redublo Quinto et al, 2007).…”
supporting
confidence: 46%
See 2 more Smart Citations
“…Angiotensin-I converting enzyme plays a key role in intrarenal vasoactive peptide systems. The enzyme transforms angiotensin I into angiotensin II inducing vasoconstriction and also inactivates bradykinin, a vasodilator peptide (Li et al, 2018). In our experiments, ACE immunolocalization was mainly present in the brush border of epithelial cells of proximal straight tubules although ACE had been localized also in mesangial cells and collecting duct (Redublo Quinto et al, 2007).…”
supporting
confidence: 46%
“…The intrarenal renin-angiotensin system may also contribute to hypertension. Renin enzyme can reach the proximal tubule that express angiotensinogen, angiotensin-I converting enzyme (ACE), and AT1 receptors in the apical domain of proximal tubule and distal convoluted tubule producing angiotensin II that contributes to hypertension through the stimulation of NaCl reabsorption in the proximal and distal convoluted tubule (Velez, 2009;Gurley et al, 2011;Li et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that single cell microinjection or microdialysis of ANG II directly into the cells may distinguish between the effects induced by extracellular ANG II from those induced by intracellular ANG II [15, 102,[174][175][176][177]. Indeed, we have demonstrated that intracellular microinjection of ANG II directly into single rabbit proximal tubule cells induced intracellular [Ca 2+ ] i responses ( Figure 3) [10,15,16,81,177]. We further reported that microinjection of the AT 1 blocker losartan abolished the [Ca 2+ ] i response induced by microinjected ANG II, but it only partially blocked the effects of extracellular ANG II [15].…”
Section: Intratubular and Intracellular Ang Ii: Intracellular Versus mentioning
confidence: 55%
“…There is accumulating evidence that ANG II acts not only as an endocrine or paracrine hormone activating cell surface ANG II receptors, but also as an intracellular or intracrine peptide activating intracellular ANG II receptors, though the precise roles of the latter remain largely unknown [9][10][11]. Indeed, in addition to activating cell surface ANG II receptors, circulating and paracrine ANG II can readily enter the cells via AT 1 receptor-mediated endocytosis.…”
Section: Introductionmentioning
confidence: 99%